Pensar el siglo XIX desde el siglo XXI : Nuevas miradas y lecturas - Peluffo, Ana (Serie Literatura y cultura., 2019)
Read as a whole, the essays in Pensar el siglo XIX desde el siglo XXI provide a fruitful discussion about the need to revise some of the canonical paradigms in Latin American nineteenth-century studies. Included in the collection are new and thought-provoking essays that attempt to go beyond the dichotomies that have characterized the cultural genealogy of the field (civilization vs barbarism, country vs. city, letter vs image, tradition vs. modernity, domestic vs. public). By bringing into the discussion recent developments in cultural studies, authors reexamine the nineteenth-century debate about the construction of nations and subjectivities from a wide range of critical perspectives.